2016
DOI: 10.1097/sle.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

ERAS Protocol Reduces IL-6 Secretion in Colorectal Laparoscopic Surgery: Results From a Randomized Clinical Trial

Abstract: ERAS protocol applied to colorectal laparoscopic surgery affects surgical stress response, decreasing IL-6 and CRP levels postoperatively and improving prealbumin postoperative synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…CRP showed the same pattern as IL-6, being lower as close as 2 hours after surgery (23) till POD 7 (17,22). Only two authors investigated the stress response dosing pituitary and adrenal hormones (16,20). Table 3 reports statistically significant results.…”
Section: Authormentioning
confidence: 84%
See 3 more Smart Citations
“…CRP showed the same pattern as IL-6, being lower as close as 2 hours after surgery (23) till POD 7 (17,22). Only two authors investigated the stress response dosing pituitary and adrenal hormones (16,20). Table 3 reports statistically significant results.…”
Section: Authormentioning
confidence: 84%
“…Results Five studies regarded patients undergoing colorectal surgery (16,(18)(19)(20)(21), one study gastric surgery (17), one study cystectomy (22) and one study retroperitoneal adrenalectomy (23). Three papers reported nutritional and immune function evaluation (17,19,20), two papers compared the differences in stress hormones response (16,20). Three papers investigated surgical impact in terms of humoral response measuring HLA-DR expression on monocyte, Immunoglobulin (Ig) or lymphocyte subpopulations (16,18,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a RCT, Mari et al [33] demonstrated that the ERAS protocol, applied to colorectal laparoscopic procedures, reduces the surgical stress response by diminishing levels of important proinflammatory elements, more specifically IL-6 and C-reactive protein. This attenuates the liver's protein synthesis switch from physiological to acute phase inflammatory proteins, allowing for an earlier liver function resumption.…”
Section: Colorectal Surgerymentioning
confidence: 99%